Hubungan antara Gaya Belajar Siswa dengan Pendekatan Pembelajaran Multiple Intelligences - Kusumawati, Nyimas Inda; Supriadi, Agus; Tendri, Muslimin (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2023)
Learning style refers to a student's preferences in obtaining and processing information, whether through sight, hearing, or physical movement. Meanwhile, the Multiple Intelligences learning approach is a learning approach that combines various aspects of learning, including combining several learning styles in the learning process. This research aims to determine the relationship between students' learning styles and Multiple Intelligences learning approaches on learning outcomes in mathematics subjects. The learning styles observed in this research are visual learning style, auditory learning style, and kinesthetic learning style. The method used in this research is descriptive analysis, where data is collected through learning style questionnaires filled out by students and the results of the students' Mid-Semester Exams. The collected data was then analyzed to see the relationship between learning styles and students' Multiple Intelligences approach. Based on the results of data analysis in two schools, it was found that students at SMP Negeri 5 Panukal were dominated by a visual learning style while students at SMK Muhammadiyah 1 Palembang were dominated by an auditory learning style. Meanwhile, students' learning outcomes at these schools are not dominated by certain learning styles. In conclusion, student learning styles have an influence on learning outcomes in mathematics subjects. Students with visual, auditory and kinesthetic learning styles have good learning outcomes. However, students' ability to combine their learning styles has a better impact on their learning outcomes. Therefore, educators need to understand the importance of Multiple Intelligence in the learning process and adapt appropriate learning methods to improve their learning outcomes.